Coolant's sloshing behavior and components' safety assessment of lead‐bismuth‐cooled reactors under seismic excitation. (29th July 2022) - Chen, Yalou; Ming, Pingjian; Yu, Guopeng; Ye, Weijie
Summary: The liquid metal fast reactor (LMFR), the most promising nuclear energy technology, has been experiencing accelerating development in recent years. Given the higher thermal conductivity of its coolant and smaller size with better portability, the current prior task of LMFR is to address its safety issue under harsh natural conditions. The sloshing behavior inside liquid metal containers under seismic excitation needs comprehensive research because of its importance to the safety and development of this technology. Lead‐bismuth‐eutectic (LBE) is well recognized as the coolant for LMFR for its chemical stability and self‐circulation advantages. Since the direct experimental research of LBE is not practical for its opacity, high melting point, and corrosivity, alternatives have been screened to assist the research. This paper focuses on the two‐phase flow behavior caused by the sloshing effect of LBE and its potential experimental alternatives, including water and mercury. A numerical study was carried out to verify the case of the "Multi‐purpose Hybrid Research Reactor for High‐tech Applications" (MYRRHA) and build the model of its upper plenum liquid lead‐bismuth container with internal components. The Volume of Fluid (VOF) method is employed based on OpenFoam. The sloshing effect of three alternative coolants was compared under the resonance excitation, operation‐based‐earthquake (OBE) excitation, and design‐based‐earthquake (DBE) excitation. Results demonstrate that the sloshing behavior of three coolants is generally in good agreement, and the complex sloshing behavior of LBE can be well predicted by water in the container. However, quantification studies of liquid levels inside the container show different relative magnitudes of three coolant alternatives under different excitation conditions. Finally, the safety of internal components has been evaluated, which shows that LBE can be well predicted by water under resonance and OBE excitation. However, the force load is underestimated during the sloshing of water under DBE excitation. Overall, water is a valid option to predict the sloshing effect of LBE unless the sloshing is violent enough. This work provides a design reference of liquid metal containers and a predictive method for coolant sloshing assessment which is critical to the safety and efficiency of the LMFR system. Abstract : A novel method is provided to study the sloshing behavior inside liquid metal containers of lead bismuth reactor under seismic excitation. Three liquid including mercury, water, and lead‐bismuth‐eutectic are employed in simulation to discussed the replaceability of lead bismuth in experiment. In addition, the safety of internal components has been evaluated, and the results show that LBE can be predicted well by water under resonance and OBE excitation but underestimated under DBE excitation.